Atomic scale Monte Carlo simulations of BF3 plasma immersion ion implantation in Si. Issue 1 (9th December 2013) - La Magna, Antonino; Fisicaro, Giuseppe; Nicotra, Giuseppe; Spiegel, Yohann; Torregrosa, Frank; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract We present a numerical model aimed to accurately simulate the plasma immersion ion implantation (PIII) process in micro and nano‐patterned Si samples. The code, based on the Monte Carlo approach, is designed to reproduce all the relevant physical phenomena involved in the process. The particle based simulation technique is fundamental to efficiently compute the material modifications promoted by the plasma implantation at the atomic resolution. The accuracy in the description of the process kinetic is achieved linking (one to one) each virtual Monte Carlo event to each possible atomic phenomenon (e.g. ion penetration, neutral absorption, ion induced surface modification, etc.). The code is designed to be coupled with a generic plasma status, characterized by the particle types (ions and neutrals), their flow rates and their energy/angle distributions. The coupling with a Poisson solver allows the simulation of the correct trajectories of charged particles in the void regions of the micro‐structures. The implemented model is able to predict the implantation 2D profiles and significantly support the process design. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)